Systematic review on stress, insomnia, and burnout syndrome in secondary school teachers (2023)
This systemic review article aimed to analyze the symptoms of stress, insomnia, and burnout syndrome in secondary school teachers. The PICO methodology was adapted for the research question and the PRISMA methodology for the article review and selection process. As a result, it was found that professional stress occurs when there is dissatisfaction or restrictions in the environment in which it is exercised; when the preparation of the person has ceased before an elaboration of organizations, as well as the deterioration of the teacher’s vitality because of the stress produced. Burnout syndrome is a reaction to chronic professional stress; the amplitudes that stand out in burnout syndrome are related to stress levels and insomnia. In conclusion, burnout syndrome tends to be more pronounced in teachers because they have direct contact with people; also, the current economic and political factors directly influence the development of their daily activity; in this way, when all these factors come together, it is possible to suffer from burnout.